The work of the peruvian church in the national social weeks (1958-2008) - Élgegren Reátegui, Fernando (2013)
This study stand out the work of the Peruvian Church as scrutinizing the signs of the times in social reality and the fidelity of his true mission meets “in favor of a society worthy of man, of his dignity  and his vocation” (Benedict XVI), shown in the ten (10) National Social Weeks made in the span of 50 years, between 1958 and 2008, the same respondents in typical of the times and contexts in which they developed. In the first part of the study presents the approaches and, in the second approach are discussed in the focus context established by the author